Symbolic Interactionism The Impact of the Advertisement "Not Smoking is Not Handsome" in the Youth Hangout - Sebayang, Muhammad Alfalah; Saragih, Jainul Ilham; Lubis, Fauziah (Judge : Jurnal Hukum, 2024)
Smoking is a bad habit that has been done since the time of the discovery of tobacco. Initially smoking only aims to warm the body but, over time the habit becomes changed goal is AS a requirement that can not be abandoned or can be said to be addicted. The majority of smokers worldwide are ± 47% male population while 12% are female population with different age categories. Various reasons people smoke a variety, among these people there are several factors that influence a person to smoke for example, prestige factors to be called “champion”, and there are also people who say smoking can trigger inspiration and keupayaan thinking, even there is an interesting pantun used Alaihi Symbolic interactionism is a sociological theory that emphasizes the role of symbols and social interaction in understanding human behavior. In the context of analyzing the influence of the “Gak ngerokok gak ganteng ” advertisement on teenage hangouts, this approach can provide a deep understanding of how the advertisement influences teenagers' perceptions, attitudes and behaviors towards smoking. In symbolic interactionism, symbols such Alaihi Salam words, images, or actions are considered to have meanings given by individuals through the process of social interaction. The “No smoking no handsome” advertisement is a symbol that gives a message to teenagers that not smoking is something cool or attractive. Through the process of social interaction, the symbol can be interpreted and interpreted by teenagers in the context of their daily lives. An analysis of the influence of these ads on teenage hangouts can involve several aspects, including: Perception and attitude, Behavior, Identity and Social Interaction. Using the framework of symbolic interactionism, the analysis can dig deeper into how the “Gak ngerokok gak tampan ” advertisement influences teenagers' mindset and behavior related to smoking, AS well Alaihi Salam how the symbols are interpreted in the cultural and social context of teenagers.